PENGEMBANGAN BUKU CERITA BERGAMBAR DIGITAL SEBAGAI MEDIA PEMBELAJARAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Maulidiya, Dina; Djuanda, Dadan; Iswara, Prana Dwija (Universitas Negeri Medan, 2024)
The lack of reading comprehension skills in grade II elementary school students is the impetus for this research because reading media has the potential to improve reading comprehension skills. Researchers developed digital picture storybooks as a tool to help students gain reading comprehension to overcome this problem. The purpose of this study is to provide details about the development of picture storybooks that researchers will make, including development design, validation results, and user responses. Design and Development (D&D) using the Analysis, Design, Development, Implementation and Evaluation (ADDIE). The resulting product was assessed by 2 material experts, 2 media experts, and 22 student users. The material expert feasibility test received an overall average score of 86.5% with the criteria œvery feasible. Then the final results of the media expert feasibility test get an overall average score of 92.5% with the criteria œvery feasible. Based on the media trial, user responses were obtained which showed an overall average score of 94.75% with œvery good criteria for picture storybooks as a learning media for reading comprehension that had been developed. This research corroborates the finding that students tend to like digital media (electronic), gadgets, and connected to the internet.